PENGARUH SUHU NOZZLE 3D PRINTING TERHADAP KEKUATAN TARIK DAN KEKERASAN PERMUKAAN FILAMEN PP DAUR ULANG - Adnan Fatchurrachman; Danar Susilo Wijayanto; Taufik Wisnu Saputra (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2026)
This study aims to investigate the effect of nozzle temperature variations on the tensile strength and surface hardness of 3D-printed specimens using polypropylene (PP) filament derived from instant noodle packaging waste. The filament was produced through an extrusion process at 200°C and subsequently printed into test specimens using Fused Deposition Modeling (FDM) with nozzle temperatures of 190°C, 200°C, and 210°C. Tensile testing was conducted in accordance with ASTM D638 Type IV, while hardness testing was performed using the Shore D method. The results show that nozzle temperature significantly affects the mechanical and physical properties of the specimens. The optimum performance was obtained at 200°C, yielding a tensile strength of 16.83 MPa and a hardness of 47.80 Shore D. At 190°C, both tensile strength and hardness decreased, while at 210°C hardness increased but tensile strength declined due to potential thermal degradation. Therefore, 200°C is identified as the optimum temperature, providing the best balance between mechanical performance and structural stability